Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan Ppkn Tema 8 Menggunakan Model Bauntung Dan Video Pembelajaran Pada Siswa Kelas V SDN Kelayan Timur 5 - Muhammad Hendra; Sulaiman (CV. ITTC INDONESIA, 2023)
The learning problem is the low student activity and learning outcomes in Civics learning. What is caused by learning is still one-way, less interesting, fun, and less meaningful for students. Efforts to overcome this by means of the BAUNTUNG model. The purpose of this research is to describe teacher activities, analyze student activities and improve learning outcomes. This study used Classroom Action Research (CAR) which was carried out in four meetings. The subjects of this study were fifth grade students at SDN Kelayan Timur 5 with a total of 25 students. This study uses qualitative and quantitative data obtained through observing teacher activities, observing student activities and written tests in groups and individually. The results of this study indicate that teacher activities were carried out with the criteria of